Development of a new Lagrangian vortex method for evaluating effects of surfaces roughness - Bimbato, A. M. [UNESP]; Alcântara Pereira, L. A.; Hirata, M. H. (Elsevier, 2019)
The main contribution of this paper is to develop a new methodology to include effects of surface roughness on aerodynamic of bodies. The numerical approach simulates the mechanism of vortex shedding of a rough circular cylinder in the subcritical flow regime (Re=105) using a mesh-free vortex method. The local turbulence effects are considered during the vorticity diffusion process; as consequence a connection between the larger scales and the smaller ones is made by eddy viscosity. The eddy viscosity computation is necessary for each Lamb vortex element that constructs the Kármán vortex street; it is also the way employed to make feasible the purposed surface roughness model. Simultaneous measurements of the spanwise-integrated unsteady aerodynamic forces and time averaged local surface pressures on a two-dimensional rough circular cylinder are investigated aiming to reach supercritical Reynolds number flow patterns from subcritical flows. It is shown that the surface roughness model captures successfully the drag crisis in a qualitative way.
Keywords: Aerodynamics of bluff body; Drag crisis; Lagrangian vortex method; Surface roughness model